Ameliorative effect of vanillin on scopolamine-induced dementia-like cognitive impairment in a mouse model - Anand, Abhinav; Khurana, Navneet; Ali, Nemat; AlAsmari, Abdullah F.; Alharbi, Metab; Waseem, Mohammad; Sharma, Neha (Frontiers in Neuroscience, 2022)
Background Alzheimer’s disease (AD) is the most common form of dementia, which is among the top five causes of death in the United States. It is a neurodegenerative disorder that causes permanent loss of memory and cognition. The current pharmacotherapy for AD is based on providing symptomatic relief only and has many side effects. There is a need for a safer, disease-modifying drug for the treatment of AD. Experimental approach The PASS online software was used to screen phytoconstituents based on their predicted effects on various AD-related targets. Vanillin was selected as the compound of interest, as it has not been researched elaborately on any animal model of AD. The acetylcholinesterase inhibitory activity of vanillin was established in vitro. Thereafter, ameliorative effect of vanillin was evaluated using the exteroceptive memory model in scopolamine-induced cognitive impairment mice model. Results Vanillin showed an acetylcholinesterase inhibitory activity in vitro, and the IC50 value was calculated to be 0.033 mM. Vanillin significantly reversed the memory and behavioral deficits caused by scopolamine as demonstrated by significant improvement in memory in negative reinforcement, elevated plus maze, and spatial learning paradigms. Vanillin also proved to have a nootropic effect. Also, vanillin proved to have significantly better antioxidant and acetylcholinesterase inhibitory effects in vivo than donepezil hydrochloride. The potential anti-AD activity of vanillin was also confirmed by the reduction in IL-6 levels and TNF-α levels. Conclusion Our results suggest that vanillin is a safe and effective natural drug candidate having a great potential for the treatment of AD. However, more research is required to evaluate its effect on A beta plaques and Tau neurofibrillary tangles in vivo.